Miniaturized Spiral Planar Inverted F Antenna of 2.4 GHz Using Design of Experiment Method for EEG-based Controlled Prosthetic Arm - Liya Yusrina Sabila; Teguh Prakoso; Munawar Agus Riyadi (National Research and Innovation Agency, 2022)
This paper presents the design of a planar inverted F antenna with a miniature or tiny shape at the frequency of 2.4 GHz. The antenna uses a spiral design to reduce the dimension of the antenna with conformal shape for a suitable prosthetic arm. Usually, the antenna design uses long experimental steps, namely trial and error. It can be summarized using the DOE (design of experiment) method. The DOE is a method to streamline the experimental steps to get the best design. The DOE method uses a tuning reference at the design parameter variation of 5 % of the nominal value. Four tuning steps can get the best results from S11, bandwidth, and gain. The designed antenna works at the resonant frequency of 2.431 GHz with the value of S11 is -22.634 dB, bandwidth of 37.1 MHz, and gain of -7.596 dBi.